2016
DOI: 10.1007/s12282-016-0666-7
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel and cyclophosphamide as neoadjuvant chemotherapy in HER2-negative primary breast cancer

Abstract: The pCR rate of TC NAC was not very high despite the high completion rate. TC NAC was effective against the triple-negative subtype, resulting in a higher pCR rate. Therefore, our results indicated that TC NAC showed limited efficacy in luminal subtype breast cancer with the exception of the triple-negative subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 17 publications
3
26
0
Order By: Relevance
“…Nakatsukasa et al enrolled 52 breast cancer patients. Of them, 94.2% (49/52) patients completed 4 TC cycles and had an overall pCR rate of 16.3% (8/49); patients with luminal A-like breast cancer (ER + , Ki67 index < 20%, HER2 negative) had a pCR rate of 0% (0/12); patients with luminal B-like breast cancer (ER + , Ki67 index > 20%, HER2 negative) had a pCR rate of 4.3% (1/23); patients with TNBC had a pCR rate of 50.0% (7/14); almost all of the pCR occurred in TNBC breast cancer patients [34]. The results showed that neoadjuvant chemotherapy with TC was more suitable for the treatment of TNBC but had limited efficacy in treating other subtypes of breast cancer.…”
Section: Cyclophosphamidementioning
confidence: 99%
“…Nakatsukasa et al enrolled 52 breast cancer patients. Of them, 94.2% (49/52) patients completed 4 TC cycles and had an overall pCR rate of 16.3% (8/49); patients with luminal A-like breast cancer (ER + , Ki67 index < 20%, HER2 negative) had a pCR rate of 0% (0/12); patients with luminal B-like breast cancer (ER + , Ki67 index > 20%, HER2 negative) had a pCR rate of 4.3% (1/23); patients with TNBC had a pCR rate of 50.0% (7/14); almost all of the pCR occurred in TNBC breast cancer patients [34]. The results showed that neoadjuvant chemotherapy with TC was more suitable for the treatment of TNBC but had limited efficacy in treating other subtypes of breast cancer.…”
Section: Cyclophosphamidementioning
confidence: 99%
“…The objective of our study was to evaluate the efficacy of prophylactic anti-allergic drug administration against TC-related skin eruption in patients with primary breast cancer. This study is a subanalysis of data that we previously reported as part of a combined phase 2 study of TC NAC and HER-TC NAC [3,4]. This study was an openlabel, nonrandomized study, which was conducted at seven different institutions.…”
Section: Methodsmentioning
confidence: 99%
“…The cumulative incidence of skin eruption every chemotherapy cycle is summarized in Figure 3. As shown in Figure 3, the onset of skin efficacy and tolerability of TC neoadjuvant chemotherapy (NAC) and HER-TC NAC in patients with breast cancer in previous studies [3,4]. Therefore, in this work, we re-analyzed the data from those studies to retrospectively evaluate the prophylactic effectiveness of anti-allergic drugs against TC/HER-TC-related skin eruption among the patients in our clinical trial.…”
Section: Skin Toxicitiesmentioning
confidence: 99%
“…Usually 600 mg/m² cyclophosphamide is intravenously (IV) administered to breast cancer patients in combination with other chemotherapeutics (Docetaxel, Paclitaxel, Doxorubicin). The recommended regimens for robustly healthy breast cancer patients include 6 cycles of cyclophosphamide, methotrexate and 5-fluorouracil (CMF) or 4 cycles of adriamycin and cyclophosphamide (AC) [71,72].…”
Section: Alkylating Agentsmentioning
confidence: 99%